2022
DOI: 10.1038/s41598-022-20812-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of restoration methods for Solidago-invaded land on soil invertebrates

Abstract: The belowground community structure of soil biota depends on plant composition and may be affected by invasive plant species. We hypothesized that the type of land restoration method applied affects the abundance and composition of soil invertebrates. Our field experiment centred on Solidago species control using different seed mixtures and methods of seed introduction (sowing mixtures: grasses, grasses with legumes, seeds from a seminatural meadow, and application of fresh hay) and different frequencies of mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Furthermore, according to our previous study on the impact of soil invertebrates, conducted in the same experimental field, it was that the season is significant concerning the abundance and number of taxa present (Perera et al, 2022). However, Ustinova et al (2022) found that S. gigantea does not favour any particular arthropod species over others for litter decomposition of the litter and does not accelerate decomposition.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Furthermore, according to our previous study on the impact of soil invertebrates, conducted in the same experimental field, it was that the season is significant concerning the abundance and number of taxa present (Perera et al, 2022). However, Ustinova et al (2022) found that S. gigantea does not favour any particular arthropod species over others for litter decomposition of the litter and does not accelerate decomposition.…”
Section: Discussionmentioning
confidence: 87%
“…Two experimental factors were drawn according to a complete randomized block design with 15 treatments in total. Each plot was 2.5 × 2.5 m (See Perera et al (2022) for further information on the experiment and seed mixtures).…”
Section: Field Experiments Design For Solidago Invaded Land Restorationmentioning
confidence: 99%